1999
DOI: 10.1055/s-1999-2676
|View full text |Cite
|
Sign up to set email alerts
|

New Results on the Functionalization of Terminal Alkenes by Cross-metathesis Reactions

Abstract: The ruthenium-catalyzed reaction of allylbenzene with several types of alkene provides good yields of the cross-metathesis products regardless of the structural characteristics of the alkene.In the course of our research on sugars we wished to prepare the mannose derivative 4. Our first approach, involving a Wittig-Horner reaction between the aldehyde 1 and the stabilized anion of phosphonate 2, afforded very low yields whatever the base and reaction conditions used. We then decided to try an intermolecular cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Among the less functionalized olefins, allylbenzene has been used as a model compound [6][7][8][9][10]. From Table 1, it appears that this reaction requires heating at 40 7C and that Grubbs I (2) and II (3) catalysts are not very efficient unless an excess of acrylonitrile or an additive such as CuCl is used.…”
Section: Cross-metathesis Of Acrylonitrile and Terminal Olefins With mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the less functionalized olefins, allylbenzene has been used as a model compound [6][7][8][9][10]. From Table 1, it appears that this reaction requires heating at 40 7C and that Grubbs I (2) and II (3) catalysts are not very efficient unless an excess of acrylonitrile or an additive such as CuCl is used.…”
Section: Cross-metathesis Of Acrylonitrile and Terminal Olefins With mentioning
confidence: 99%
“…This reaction was first reported in 1995 in the presence of the Schrock molybdenum catalyst [Mo(CHCMe 2 Ph)(NAr)][-OCMe(CF 3 ) 2 ] 2 1, which made the cross-metathesis with simple terminal alkenes and O-protected o-hydroxyalkenes possible in excellent yields [4]. The first-generation Grubbs catalyst RuCl 2 (=CHPh)(PCy 3 ) 2 2 generally exhibited a poor reactivity in cross-metathesis reactions with conjugated olefins such as acrylonitrile or acrolein [5], and the crossmetathesis of acrylonitrile with allylbenzene in 60% yield represents one of the rare examples of acceptable reactivity with this catalyst [6]. Then, the development of crossmetathesis with acrylonitrile and a variety of functional terminal olefins started with the introduction of Grubbs secondgeneration RuCl 2 (=CHPh)(PCy 3 )(N-heterocyclic carbene), and more robust Hoveyda-type catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of material on this potentially important reaction would seem to point towards incompatibility; however, two reports have appeared which cast doubt on this conjecture, at least in the case of certain substrates. Castedo and Blanco [21] found that allylbenzene could efficiently react with a range of CM partners (2 equiv), including acrylonitrile or acrolein, in the presence of 6 (5 mol %). This report also detailed the first example of CM with allyl bromide catalyzed by 6.…”
Section: Selectivity-new Developments With [Cl 2 (Pcy 3 ) 2 Ru¼chph]mentioning
confidence: 99%
“…If one sees a typical CM reaction as a competition between three reaction pathways, that is, selective CM or dimerization of either starting material, then if one partner dimerizes relatively slowly, the selectivity naturally increases. The first such report came from Grubbs and co-workers at Caltech, [32] who observed that CM between a,b-unsaturated compounds (esters, aldehydes, [33] and ketones [19][20][21][22][23][24] and simple terminal olefins 16-18 in the presence of 3 (5 mol %) in CH 2 Cl 2 at 45 8C proceeded in good to excellent yields with impressive E selectivity ( Table 2). In most cases, an excess of one olefin component is used to improve selectivity.…”
Section: Selectivity With Electron-withdrawing Alkenes : Imes-based Cmentioning
confidence: 99%
“…The example of CM between allylbenzene, a type I olefin, and allyl bromide, promoted by Gru-I, was published by Castedo et al (Scheme 12). 31 Further improvements in terms of yield were made by using the more active Gru-II, 32,33 Hov-II, 34 and finally Est-II 35 catalysts. It was noted that the internal alkene 39 can act as a convenient replacement for the more volatile allyl chloride.…”
Section: CMmentioning
confidence: 99%